Drag and drop the correct steps to solve the equation for x. Make sure to put the steps in order. Not all steps listed will be used.

12 - 3x = 8 - 4(2x - 6)

1 answer

1. Distribute the 4 to both terms inside the parentheses: 4(2x - 6) = 8x - 24.
2. Combine like terms on both sides of the equation: 12 - 3x = 8x - 24.
3. Simplify the equation by combining like terms: -3x - 8x = -24 - 12.
4. Simplify the equation further: -11x = -36.
5. Divide both sides of the equation by -11 to isolate x: x = -36 / -11.
6. Simplify the expression on the right side of the equation: x = 36/11.